CORPORATE COOPERATION WITH COOPERATIVES IN THE AGRIBUSINESS SECTOR: AN ANALYSIS OF FORMS AND PROTECTION OF STATE LAW - siti mariyam (Journal Philosophy of Law, 2021)
This study aims to examine and analyze the form of cooperative relationships between companies and cooperatives that use the principle of partnership in agribusiness and how the legal protection of the state against cooperatives in cooperation with companies in the field of agribusiness. This study uses normative juridical research methods. Normative juridical research is research that utilizes secondary data and primary data as the main data. This study uses an empirical juridical approach and a statutory approach, which in the discussion of this study will use descriptive analysis to describe the findings in the field. The results of the study indicate that at this time, cooperation between companies and cooperatives that use the principle of partnership in the field of agribusiness can be carried out in aspects such as capital, technology, marketing, production facilities, production processes, product processing, and so on, while the form of state legal protection that the state must implement against cooperatives in cooperation with companies in the agribusiness sector is in the form of preventive legal protection from the government, namely in terms of price determination, such as determining interest on capital loans to determining market prices.